Impact Of Land Privatization For Coastal Communities On Kapoposang Island, Pangkep: Government's Maritime Diplomacy Efforts - Brandy Emerson Ridho; Seniwati Seniwati (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
Land privatization, especially on Indonesia's small islands, has sparked conflict between local communities and private companies, who often fight over land that residents previously used to earn a living. This practice not only damages the environment but also threatens the socio-cultural values ​​of the community, because their access to natural resources and markets is limited. Land privatization has become a rampant problem in Indonesia. This journal focuses on land privatization on Kapoposang Island. The aim of this research is to identify the impact of land privatization on the people of Kapoposang Island and maritime diplomacy efforts on this issue. This journal uses two theories, namely the theory of land privatization and also the theory of maritime diplomacy. The method used is the interview method. The author analyzes various news sources and checks them with interview results obtained from the field. The results of the analysis show that the people of Kapoposang Island are affected by impacts such as slow economic growth and its correlation with social inequality among the community. The government's maritime diplomacy efforts are not running smoothly because the security sector which is supposed to be guarded by the government is not running in line with the public's expectations. This privatization of land can also have an impact on the economic sector, especially, the economic growth of local communities which can be hampered due to land acquisition and imbalance in market competition.